The end of globalization : lessons from the great depression - James, Harold, 1956- 1956- (Harvard Univ. Press, 2001)
"In this book. Harold James provides a sobering historical perspective, exploring the circumstances in which the globally integrated world of an earlier era broke down under the pressure of unexpected events." "James examines one of the great historical nightmares of the twentieth century: the collapse of globalism in the Great Depression. Analyzing this collapse in terms of three main components of global economics - capital flows, trade, and international migration - James argues that it was not simply a consequence of the strains of World War I but resulted from the interplay of resentments against all these elements of mobility as well as from the policies and institutions designed to assuage the threats of globalism. There are significant parallels today highly integrated systems are inherently vulnerable to collapse, and world financial markets are vulnerable and unstable."--BOOK JACKET.